Application of Buddhist Philosophy in Nepal: A General Review - Sharma-Gautam, Shankar Prasad (Research Nepal Journal of Development Studies, 2022)
The application of Buddhist Philosophy in Nepal can be analyzed in Economic Development, Gender Studies, Livelihood, Peace, Spirituality, Sustainable Development, Tantrism, Tourism, and many more. To find out the application of Buddhism in Nepal the study has been conducted. The philosophy of peace, reality, love, and compassion are universal. Thus Buddhism is a practical philosophy of the middle way path of humanity. Thus it is applicable everywhere. The study is the general review of selected research conducted in Nepal. It is a qualitative descriptive content review of the list presented in reference. Thus in conclusion Buddhism is a way of peaceful life. It is applicable in every sector of development and humanity.